Probiotic products consuming analysis with a university education institution students (Research, Society and Development, 2021)
Health care and attention to lifestyle habits have been gaining attention in recent years and the change in eating habits is relevant since the inclusion of some foods can help maintain health. Among these foods, probiotics are highlighted, which through microbial action help in beneficial activities of the digestive and immune systems. The objective of this work was to investigate the knowledge and behavior of consumption of probiotic foods by students from a higher education institution and to verify the judgment of a proposed purchase intention of kefir based on passion fruit albedo. The research participants were 327 students from a Higher Education Institution who answered an online questionnaire, published in WhatsApp groups and institutional emails. The responses obtained were tabulated and analyzed qualitatively and quantitatively. Most research participants (72.8%) were aged between 18 and 24 years old, where 32.1% have an income between R$ 1100.00 and R$ 2200.00, the participants have a sedentary routine, but without health problems. Part of the students correctly defined “probiotic foods”, having habits of consumption every six months, with fermented milk as the main insertion and frequency food, and more preferably yogurt. Participants do not know or consume the Kefir product, preferring functional foods based on milk, slightly acidic and are open to the proposal to purchase a Kefir based on passion fruit albedo, requiring product development and sensory tests.